Environmental monitoring solution for cultural heritage. Issue 1 (1st April 2022) - Lombardo, L.; Parvis, M.; Grassini, S.; Angelini, E.
Abstract: Environmental monitoring is crucial factor in the safeguard and conservation of the cultural heritage. Unsuitable environmental conditions can easily accelerate the degradation of several materials and, as consequence, damage the stored artifacts. Moreover, environmental conditions can easily change in an unpredictable way and, therefore, the employment of an environmental monitoring system is mandatory in almost all locations, including museums, storage rooms and outdoor exhibitions. This paper tries to explain the main constraints required for environmental monitoring in the cultural heritage field. Moreover, a novel distributed monitoring system, developed at Politecnico di Torino, is described and compared to several solutions that are commercially available. The proposed solution demonstrated excellent characteristics which satisfy the requirements of environmental monitoring in the cultural heritage at a very competitive cost.